KORELASI GAYA PENGASUHAN PADA REGULASI EMOSI ANAK USIA GOLDEN AGE : SYSTEMATIC LITERATURE REVIEW - Putri Diahayu; Keysha Fairuzia; Clinton Pitoyo; Irene Maharani; Talitha Nasywa (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This systematic literature review examines the correlation between parenting styles and emotion regulation in children aged 0-5 years (golden age). Following PRISMA protocol, 11 articles from Scopus database (2021–2025) were analyzed. Authoritative parenting showed significant positive correlation with adaptive emotion regulation, including constructive emotional expression and self-recovery capacity. Authoritarian parenting negatively correlated with emotion regulation, associated with emotional suppression. Permissive parenting yielded variable outcomes depending on family context. Cross-cultural findings indicate universal neuropsychological mechanisms yet culturally-influenced expressions. Authoritative parenting emerges as the most consistent protective factor for emotion regulation development in early childhood.